10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundResidential care facilities (RCFs) have become central sites of institutional dying in aging societies, yet the psychological preparedness of RCF professionals remains insufficiently examined. Death attitudes represent a critical workforce variable with implications for care quality and organizational sustainability.MethodsA cross-sectional study included 623 professionals working in Portuguese RCFs. Participants completed the Death Attitude Profile-Revised and a sociodemographic questionnaire. Exploratory factor analysis confirmed the five-factor structure, and nonparametric tests examined determinants of death attitudes.ResultsAge, education, professional role, and religious affiliation significantly shaped death attitudes. Older professionals demonstrated greater acceptance but persistent avoidance. Higher education was associated with lower avoidance and escape-oriented attitudes, while years of experience in RCFs showed no independent effect.ConclusionsPsychological adaptation to institutional mortality in RCFs depends more on educational and existential resources than exposure duration alone, underscoring the need to integrate structured death education into workforce development and governance strategies.